Dominansi Jenis-Jenis Tanaman Sayur Introduksi di Pasar Sayuran Kota Bengkulu - Wiryono, Wiryono; Nurliana, Steffanie (Life Science, 2019)
Since the beginning of agriculture revolution several thousand years ago, human has distributed food plant species far beyond their natural range. The tendency of agriculture practice to plant certain â€œsuperiorâ€ species and varieties has led to the homogenization of dominant food plant commodities worldwide. Local species and varieties are marginalized with the introduction of exotic species, resulting in the decline of genetic diversity. The objectives of this study were: 1) to determine the species richness of vegetable plants in three traditional markets in Bengkulu City, 2) to know the species composition of the vegetable plants in those markets, and 3) to determine the species similarity index among the three markets. Data were gathered by recording all species of vegetable plants in the markets. The data were, then, analyzed to determine the species richness, species composition and species similarity among the three markets. The results showed that 1) the total number of vegetable plant species in the three markets was 50, consisting of 23 families, 2) the introduced species dominated the composition of vegetable plants, and 3) the similarity index among markets were >90%. These results confirm the tendency that food plant species composition is dominated by few species only, and show that the species composition of vegetable plants among markets in Bengkulu city was highly similar. Keywords: biodiversitas, ethnobotani, ketahanan pangan. Sejak dimulainya revolusi pertanian beberapa ribu tahun yang lalu, manusia telah memperluas penyebaran jenis tanaman pangan sampai jauh dari wilayah sebaran aslinya. Kecenderungan praktek pertanian yang menanam jenis-jenis dan varietas â€œunggulâ€ menyebabkan terjadinya keseragaman jenis dan varietas tanaman yang mendominasi komoditas tanaman pangan di seluruh dunia. Jenis-jenis dan varietas tanaman lokal banyak yang tersingkir oleh jenis-jenis introduksi, sehingga terjadi penurunan keragaman genetis. Penelitian ini bertujuan untuk menghitung kekayaaan jenis dan komposisi jenis tanaman sayur segar yang terdapat di tiga pasar di Kota Bengkulu. Data jenis sayuran diperoleh dari pencatatan di lapangan. Data diolah untuk menghitung kekayaan jenis tanaman, menentukan dominansi jenis tanaman berdasarkan frekuensi ditemukannya, dan menghitung indeks kemiripan jenis antara ketiga pasar. Hasil penelitian menunjukkan bahwa 1) jumlah seluruh jenis tanaman sayur di tiga pasar adalah 50 jenis yang terdiri dari 23 suku; 2) jenis-jenis tanaman yang mendominasi komposisi jenis tanaman sayur di pasar adalah jenis-jenis introduksi, dan 3) indeks kemiripan komposisi jenis tanaman sayur antara pasar > 90%. Hasil penelitian ini mengkonfirmasi kecenderungan bahwa komposisi jenis tanaman pangan didominasi oleh hanya sedikit jenis tanaman, dan menunjukkan bahwa komposisi jenis tanaman pangan antar pasar di Kota Bengkulu sangat mirip. Kata kunci: biodiversitas, ethnobotani, ketahanan pangan